A novel group ownership proof and transfer scheme for B2B, B2C and C2C transactions. (2018) - Tsai, Meng-Lin; Chen, Yu-Yi
In the field of supply chain management, radio frequency identification (RFID) tags have attracted widespread popularity. As raw materials or products are purchased, an inventory flow for products is completed once the ownership is transferred to the customer. On the basis of RFID tagged inventory, ownership transfer is a critical issue. The ownership of RFID tagged items should be seamlessly transferred. This paper proposes a novel RFID ownership transfer scheme suitable for products with multiple components attached with tags that need to be shipped together as a group. This is the first group ownership transfer scheme to emphasis the proof of ownership is crucial to purchase reliability. Buyers can confirm that the seller is the owner before the purchase. The ownership of the product can be verified and then be transferred successfully in business-to-business (B2B), business-to-customer (B2C) and customer-to-customer (C2C) transactions.